Fine needle diathermy - A choice for managing corneal vascularization - Thatte, S (Nepalese Journal of Ophthalmology, 2011)
Introduction: Corneal vascularization develops as a result of various corneal diseases. Fine- needle diathermy (FND) is one of the methods to occlude corneal vessels. Objective: To evaluate the efficacy and safety of this method in a series of patients with corneal vascularization. Materials and methods: Twenty eight patients with corneal vascularization were treated with FND. The patients were divided into four groups according to etiological factors like pre-keratoplasty (high risk patients), increased keratopathy, recurrent inflammation and postkeratoplasty rejection .The FND was performed under local anaesthesia with the help of a corneal needle of 10-0 monofilament nylon suture. The success of treatment was evaluated in terms of regression and occlusion of corneal vessels. Results: The main aim of a complete occlusion of blood vessels was achieved in all patients. The most frequent complication seen was a transient whitening of the cornea especially around the needle entry in nine cases, which cleared within 24 hours. Conclusion: FND is a simple safe, inexpensive and effective treatment. It can be repeated and used as an alternative therapy for corneal vascularization. Key words: fine needle diathermy; corneal vascularization; occlusion of vessels; prekeratoplasty DOI: 10.3126/nepjoph.v3i1.4274 Nepal J Ophthalmol 2011;3(5):23-26